Further insight on recombination losses in the intrinsic layer of a-Si:H solar cells using computer modeling tools - Rubinelli, Francisco Alberto (2017)
Recombination losses of a-Si:H based p-i-n solar cells in the annealed state are analyzed with device computer modeling. Under AM1.5 illumination, the recombination rate in the intrinsic layer is shown to be controlled by a combination of losses through defect and tail states. The influence of the defect concentration on the characteristic parameters of a solar cell is analyzed. The impact on the light current-voltage characteristic curve of adopting very low free carrier mobilities and a high density of states at the band edge is explored under red and AM1.5 illumination. The distribution of trapped charge, electric field, and recombination loses inside the intrinsic layer is examined, and their influence on the solar cell performance is discussed. Solar cells with intrinsic layers deposited with and without hydrogen dilution are examined. It is found that the photocurrent at −2 V is not always a good approximation of the saturated reverse-bias photocurrent in a-Si:H p-i-n solar cells at room temperature. The importance of using realistic electrical parameters in solar cell simulations is emphasized.